(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Aims to understand the changes in meteorological factors affecting the number of dengue hemorrhagic fever cases in Da Nang city, period 2015-2022. Method: Research using weekly secondary data on the number of dengue hemorrhagic fever cases and meteorological factors (average temperature, relative humidity, wind speed, cumulative rainfall); carry out descriptive steps and analysis of correlation and Poisson regression to find out the relationships. Results: The study showed that there is a correlation between weekly average temperature, weekly average relative humidity and accumulated rainfall with the number of dengue hemorrhagic fever cases by week (p < 0.05). Conclusion: It is necessary to have dengue prevention measures in accordance with changes in meteorological factors while forecasts of weather changes and climate changes are becoming more and more accurate.